2022
DOI: 10.31392/iscs.2022.21.088
|View full text |Cite
|
Sign up to set email alerts
|

Future preschool teachers’ professional competence in planning, implementing and evaluating the learning process

Abstract: One of the most important tasks in the 2022 UNESCO report is the preparation of teachers in the field of higher education, which is oriented towards the improvement of professional competence. The teacher is described as a creator of knowledge, and as a central person in educational and social transformation, while knowledge and learning are described as the basis of renewal and transformation. Opportunities for meaningful and high-quality education should be available at every stage of a person's life. Presch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…It is indicated that new teachers have good theoretical knowledge, but they lack the readiness to solve real pedagogical problems to overcome challenges in the dynamic and changing educational environment (Newberry & Allsop, 2017;Smets & Struyven, 2020;Karlberg, & Bezzina, 2022;Ndebele et al, 2023). Teacher education programs play a significant role in building the professional competence of new teachers in order to develop the skills necessary for effective teacher activity in school (Sandholtz, 2011;Caena, 2014;Barak, 2017;Āboltiņa, et al, 2024). During the study process, during pedagogical practice, and in work-based studies, future teachers have the opportunity to see real problems in school life and offer solutions to them that help to overcome the gap between theory and practice (Kennedy, 2016;Yuan, & Lee, 2016;European Commission, 2017;Šūmane, & Āboltiņa, 2023Šūmane, & Āboltiņa, , Hamaidi, et.al., 2014.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is indicated that new teachers have good theoretical knowledge, but they lack the readiness to solve real pedagogical problems to overcome challenges in the dynamic and changing educational environment (Newberry & Allsop, 2017;Smets & Struyven, 2020;Karlberg, & Bezzina, 2022;Ndebele et al, 2023). Teacher education programs play a significant role in building the professional competence of new teachers in order to develop the skills necessary for effective teacher activity in school (Sandholtz, 2011;Caena, 2014;Barak, 2017;Āboltiņa, et al, 2024). During the study process, during pedagogical practice, and in work-based studies, future teachers have the opportunity to see real problems in school life and offer solutions to them that help to overcome the gap between theory and practice (Kennedy, 2016;Yuan, & Lee, 2016;European Commission, 2017;Šūmane, & Āboltiņa, 2023Šūmane, & Āboltiņa, , Hamaidi, et.al., 2014.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Competences that teachers require must be altered and enhanced to provide opportunities for educating 21st-century learners (Caena and Redecke, 2019;Rubene et al, 2021a;Sarva et al, 2023). Teachers need to be capable of adapting their teaching style to align with the diverse needs of students and foster the engagement of all learners in the educational process (Aboltina et al, 2022). Within a classroom, there may be students from various cultures with different religious beliefs, languages, learning abilities, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of higher professional education in the 21st Century is to prepare qualified, competitive specialists for the labour market who are able to work effectively in their field at a world standard level, ready for social and professional mobility, continuous professional growth and possessing appropriate professional competences (Kaļķe et al, 2022). Professional competence is developable, variable, dependent on the context, on an individual's habits of mind, attention, critical thinking, and self-awareness.…”
Section: Introductionmentioning
confidence: 99%